Licks and modal harmony of Herbie Hancock’s ‘So What’ / Muhamad Haris Arifin - Arifin, Muhamad Haris (2020)
This paper reviews the common licks used by Herbie Hancock and the modal harmony used by Herbie Hancock in “So What”. The data collected were from modern piano major bachelor students from Faculty of Music, UiTM Shah Alam. This study shows the significance of improvisation ideas using the right harmony, licks and the way to implement them to make the musical works rich in jazz criteria and knowledge. In addition, the findings of this study shows the major problems encountered by students in improvise in this song. Next, the study shows the examples of licks and scales that can be use in “So What”.